Acetaminophen as a renoprotective adjunctive treatment in patients with severe and moderately severe Falciparum malaria: a randomized, controlled, open-label trial - Plewes, K; Kingston, HWF; Ghose, A; Wattanakul, T; Hassan, MMU; Haider, MS; Dutta, PK; Islam, MA; Alam, S; Jahangir, SM; Zahed, ASM; Sattar, MA; et al. (Oxford University Press, 2018)
Acute kidney injury independently predicts mortality in falciparum malaria. It is not known whether acetaminophen's capacity to inhibit plasma hemoglobin-mediated oxidation is renoprotective in severe malaria.A phase 2, open-label, randomized controlled trial at two hospitals in Bangladesh was conducted to assess effects on renal function, safety, pharmacokinetic properties and pharmacodynamic effects of acetaminophen. Febrile patients ( >12 years) with severe and moderately severe falciparum malaria were randomly assigned to receive acetaminophen (1g 6-hourly for 72 hours) or no acetaminophen, as an adjunct to intravenous artesunate. Primary outcome was the proportional change in creatinine after 72 hours stratified by median plasma hemoglobin.Between July 2012 and September 2014, 62 patients were randomly assigned to receive acetaminophen (n=31) or no acetaminophen (n=31). Median (interquartile range) reduction in creatinine after 72 hours was 23% (37 to 18%) in patients assigned to acetaminophen, versus 14% (29 to 0%) in patients assigned to no acetaminophen (p=0.043). This difference in reduction was 37% (48 to 22%) versus 14% (30 to -71%) in patients with plasma hemoglobin ≥45,000 ng/mL (p=0.010). The proportion of patients with progressing acute kidney injury was higher among controls (subdistribution hazard ratio, 3.0; 95% CI, 1.1 to 8.5; p=0.034). Pharmacokinetic-pharmacodynamic analyses showed that higher exposure to acetaminophen increased the probability of creatinine improvement. No patient fulfilled Hy's Law for hepatotoxicity.In this proof-of-principle study, acetaminophen showed renoprotection without evidence of safety concerns in patients with severe falciparum malaria, particularly in those with prominent intravascular hemolysis.